Translational model systems for complex sodium channel pathophysiology in pain - Schrenk-Siemens, Katrin; Rösseler, Corinna; Lampert, Angelika (Voltage-gated sodium channels: structure, function and channelopathies, 2018)
Chronic pain patients are often left with insufficient treatment as the pathophysiology especially of neuropathic pain remains enigmatic. Recently, genetic variations in the genes of the voltage-gated sodium channels (Navs) were linked to inherited neuropathic pain syndromes, opening a research pathway to foster our understanding of the pathophysiology of neuropathic pain. More than 10 years ago, the rare, inherited pain syndrome erythromelalgia was linked to mutations in the subtype Nav1.7, and since then a plethora of mutations and genetic variations in this and other Nav genes were identified. Often the biophysical changes induced by the genetic alteration offer a straightforward explanation for the clinical symptoms, but mutations in some channels, especially Nav1.9, paint a more complex picture. Although efforts were undertaken to significantly advance our knowledge, translation from heterologous or animal model systems to humans remains a challenge. Here we present recent advances in translation using stem cell-derived human sensory neurons and their potential application for identification of better, effective, and more precise treatment for the individual pain patient.
Gesehen am 27.04.2020